Foundations of sport and exercise psychology - Weinberg, Robert S.; Gould, Daniel (United States : Human Kinetics, 2015)
As the leading text in sport and exercise psychology, "Foundations of sport and exercise psychology", provides a through introduction to key concepts in the field. It offers both students and new practitioners a comprehensive view of sport and exercise psychology, drawing connections between research and practice and capturing the excitement of the world of sport and exercise.
Includes bibliographical references and index.
Keywords: Sports -- Psychological aspects; Exercise -- Psychological aspects